PENERAPAN MODEL KOOPERATIF LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS III SD NEGERI 50 KOTA TERNATE - Naser, Umihani (Universitas Khairun, 2024)
The purpose of this study was to describe the process of the STAD (Student Team Achievement Division) cooperative learning model in Class III Students of SD Negeri 50 Kota Ternate, and to describe the learning outcomes of Class III students of SD Negeri 50 Kota Ternate, after using the STAD type cooperative learning model in Cooperation in Various Environments. This research is Classroom Action Research (CAR). The subjects of the study were class III students with a total of 17 students consisting of 14 males and 3 females. Data collection techniques in this study were observation, documentation and tests. Data analysis techniques in this study were carried out in three stages, namely to determine the completeness of student learning outcomes individually, to determine the completeness of student learning classically and to calculate the percentage of student and teacher activity results.The results of this study indicate an increase in each cycle, where cycle I obtained learning completeness with a percentage of 47.05% as many as 8 students, teacher activity 58.09% and student activity 59.37%. Then in cycle II, student learning completion was obtained with a percentage of 76.47% of students, teacher activity increased to 81.81% and student activity 81.25%. Thus, it can be concluded that learning using the Student Teams Achievement Division (STAD) Cooperative Model in social studies learning can improve the learning outcomes of grade III students of SD Negeri 50 Kota Ternate.